O duplo e o mal na constituição da personagem: vestígios de uma construção do fantástico em O homem duplicado, de José Saramago - Lima, Rosângela Soares de (2019)
In this study, a reading on José Saramago's O homem duplicado (2002) is elaborated, having as themes the evil and the double in the constitution of the main characters in the work, in order to understand how they are presented in the novel based on studies of Rosenfeld (2005) and Candido (2005). At the same time, we also analyze the aesthetics of the fantastic in the narrative, discussing the possible meanings of the elements used. For this, we start from the reflections developed in studies by França (2009), Roas (2014) and Arnaut (2008). It is understood that, with fantastic aesthetics, Saramago brings the reader closer to fictional worlds without distancing them from reality. Constructing situations with the insertion of the uncanny, the writer broadens the reading perspective and opens a range of implicit meanings for the narrative that problematizes the life of the contemporary man. It is thus through the fantastic aesthetics that the expression of human cruelty is presented and thus linked to the theme of evil since absolute disorder illustrates evil itself. Understanding what is evil in contemporary times helps in understanding human nature, which in turn is presented in the narrative. In O homem duplicado, the figuration of the liquid human being, to use Bauman's terms (2007), is created in the unrest of a society that values appearance even more. The recreations of the thematic of the double are directly linked not only to the human need to maintain the myth but to debate and discuss issues such as of the being and the appearance. Saramago's approach to this theme, reinvented with his own language and narrative engagement, satisfactorily illustrates our society. His literary project has always focused on the social issue, and once again, the novel under study highlights his critical way of narration, and is thus evidenced and reinforced by the construction of the fantastic. In terms of methodology, the actions and behaviors of the central characters were focused, as well as the constitution of the double in them, to discuss the relations with the evil theme Bataille (1989), Augustine (1980, 2004), Ricoeur (2013). It is worth adding that to support the theoretical considerations about the double, we studied authors that move through philosophy such as Plato (2010), Rosset (1988) and Camus (2005), through psychology and psychoanalysis such as Rank (2013) and Freud (2008) and sociology (Bauman, 2004, 2005, 2007, 2008, 2009), Bauman; Raud (2018) and Bauman; Donskis (2019).